Designing NGO Interventions in Forest Commons of the Western Ghats, India: Is it Possible to Avoid Institutional Panaceas While Using Design Principles? - Anushri Narayan Visweswaran; Frank van Laerhoven (International Journal of the Commons, 2024)
Scholarship shows that community forests can be sustainably self-governed through collective action. In the Western Ghats (India), many NGOs have risen to support communities with this task. Few scientific studies explore NGO interventions in CPR governance. As a result, we observe a risk of over-generalising scientific knowledge over many different contexts when designing interventions, resulting in prescriptive institutional panaceas. We ask: Can design principles be applied by practitioners, NGOs in particular, in designing forest CPR interventions while avoiding institutional panaceas? We identified 12 design principles for sustainable community CPR governance in literature. We compared these conditions against NGO interventions in the Western Ghats. Data was collected through semi-structured interviews and document analysis of 10 NGOs. We found that NGOs applied most design principles through a range of particular activities. By combining these activities in different ways based on local contexts and intervention stage, we show how the concern about over-generalisation of design principles could be avoided.